Fear appeal approach for a political campaign published in Utusan Malaysia and Harakah during the 13th General Election / Nor Azni Ahmad Husairi and Mohammad Yaacob - Ahmad Husairi, Nor Azni; Yaacob, Mohammad (CMIWS and UiTM Press, 2014)
Previous studies have shown the ability of fear appeal in influencing voting behaviour among citizens (Jerit, 2004). During the 15-day campaign period of 13th Malaysian General Election (GE13), candidates from Barisan Nasional (BN) and Pakatan Rakyat (PR) tended to induce fear appeal into the stories reported by newspapers that support them, namely Utusan Malaysia and Harakah, respectively. This study seeks to investigate the characteristics of fear appeal in both the newspapers, the genre of news and articles that comprise the fear appeal, relationships between the genre of news and articles with characteristics of fear appeal, and differences in the way political fear appeal was employed in the content of both newspapers.